2022
DOI: 10.1002/jpen.2319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber on gut barrier function, gut microbiota, short‐chain fatty acids, inflammation, and clinical outcomes in critically ill patients: A systematic review and meta‐analysis

Abstract: Background: Although some studies have explored the relationships between dietary fiber (DF) supplement and gut barrier function, changes of gut microbiota, and clinical outcomes in critically ill patients, the results were not consistent. Objective:The purpose was to explore the effect of DF on gut barrier function, gut microbiota, short-chain fatty acids (SCFAs), inflammation, and clinical outcomes in critically ill patients. Methods:A search was performed through five databases from inception to July 12, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
(298 reference statements)
1
17
0
Order By: Relevance
“…Our study results contradict a previous meta-analysis published in 2015, in which the benefit of fiber supplementation was observed only in non-critically ill patients and not in the ICU setting (34). Nevertheless, the current study results on the benefit of fiber supplementation in critically ill patients were consistent with a recent meta-analysis of dietary fiber in critical care patients published in 2021 (35). From our point of view, differences in the results between our meta-analysis and the prior meta-analysis by Kamarul Zaman et al (34) might be due to differences in the study inclusion criteria, as we only included randomized control studies, and seven RCTs conducted after 2015 were added to our recent meta-analysis.…”
Section: Figuresupporting
confidence: 92%
“…Our study results contradict a previous meta-analysis published in 2015, in which the benefit of fiber supplementation was observed only in non-critically ill patients and not in the ICU setting (34). Nevertheless, the current study results on the benefit of fiber supplementation in critically ill patients were consistent with a recent meta-analysis of dietary fiber in critical care patients published in 2021 (35). From our point of view, differences in the results between our meta-analysis and the prior meta-analysis by Kamarul Zaman et al (34) might be due to differences in the study inclusion criteria, as we only included randomized control studies, and seven RCTs conducted after 2015 were added to our recent meta-analysis.…”
Section: Figuresupporting
confidence: 92%
“…In the E-DIITM, fiber is considered one of the factors that reduce diet-related inflammation. In previous studies, an adequate fiber intake was shown to be important in maintaining low CRP levels and in maintaining homeostasis of the gut microbiota [ 81 ]. A high UPF consumption can also lead to deficiencies of micronutrients considered to be anti-inflammatory factors in the diet, such as magnesium, vitamin C, vitamin D, zinc and niacin [ 82 ].…”
Section: Possible Mechanisms Explaining the Relationship Between Upf ...mentioning
confidence: 99%
“…In fact, it has been suggested that a diet rich in fiber can decrease the systemic inflammatory response by improving the intestinal barrier function and modulating the intestinal microbiota [ 81 ]. This is because dietary fiber is essential for the formation of SCFAs, which are thought to play a key role in neuroimmunoendocrine regulation [ 106 ].…”
Section: Possible Mechanisms Explaining the Relationship Between Upf ...mentioning
confidence: 99%
“…The benefit from providing dietary fiber in critical illness is well documented in clinical studies. 10 Inflammatory markers including TNF-α, IL-6, and procalcitonin have been shown to be no different on admission to the ICU between patients who are critically ill and receiving a fiber-containing formula vs fiber-free formula but are significantly reduced in the group receiving the fibercontaining formula to significantly lower levels by the end of the second week. Serial levels of C-reactive protein show similar results, no different upon admission to the ICU between patients receiving a fiber-containing vs fiber-free formula but significantly lower levels by day 15 in the group receiving dietary fiber.…”
Section: Clinical Benefits From the Provision Of Dietary Fiber In The...mentioning
confidence: 99%